Ampal-American Israel Corp., EGI-Fund (08-10) Investors LLC, EGI-Series Investments LLC, BSS-EMG Investors LLC and Fischer v. Arab Republic of Egypt. (2022) - Unknown
Abstract : 406 Jurisdiction – Foreign investor – Foreign control – Substantial interest – Whether the investors satisfied the conditions of nationality under the BIT – Whether nationals of the home State had a substantial interest in the investors – Whether a substantial interest needed to be a controlling or a majority interest Jurisdiction – Foreign investor – Denial of benefits – Requirement to consult – Whether the host State promptly consulted the home State to seek a mutually satisfactory resolution of the matter – Whether exercising a denial-of-benefits clause amounted to withdrawing unilaterally a previously given consent – Whether the denial-of-benefits clause could be exercised after the investment claim had been filed Jurisdiction – Investment – Indirect investment – Burden of proof – Whether an investor proved its alleged beneficial interest in an investment through a corporate vehicle Jurisdiction – Consent – Contract claims – Whether the claim was purely contractual – Whether the investors submitted a treaty claim Jurisdiction – Consent – Exclusions and reservations – Taxation measures – Whether a carve-out clause for taxation barred the investors' claims of expropriation Jurisdiction – Investment – Legality – Corruption – Public policy – Burden of proof – Whether the State discharged its burden of proof in establishing that the investment was illegal and made in corrupt circumstances Admissibility – Abuse of process – Whether resorting to four parallel arbitrations with the same factual matrix, same witnesses and many identical claims was abusive – Whether the nature of those parallel claims was identical – Whether pursuit of the same claim before different investment tribunals should be allowed – Whether an investor should make an election to resolve overlapping claims in parallel proceedings State responsibility – Attribution – State-owned entity – Contract – ILC Articles on State Responsibility, Article 4 – ILC Articles on State Responsibility, Article 5 – ILC Articles on State Responsibility, Article 8 – ILC Articles on State Responsibility, Article 11 – Whether the State was liable for contractual obligations undertaken by two State entities Expropriation – Compensation – Legal stability – Tax exemption – Whether a licence granting taxation privileges constituted a protected investment – Whether the revocation of a licence constituted an expropriation – Whether the investors had the right to retain the taxation privileges beyond the initial period of the licence 407 Full protection and security – Due diligence – Civil unrest – Whether the State took reasonable precautionary, preventive and remedial measures to protect the physical security of a pipeline network from sabotage Procedure – Res judicata – Contract – Privity of interest – Force majeure – Whether the factual findings on the sabotage of a pipeline network in a parallel commercial arbitration were binding on the tribunal – Whether the legal findings on contractual termination in a parallel commercial arbitration were binding on the tribunal Expropriation – Unlawful expropriation – Contract – Whether State entities wrongfully terminated a contract under the proper law – Whether unlawful termination of a contract was tantamount to an unlawful expropriation